Mathematical Connection Ability of Grade 8th Students’ in terms of Self-Concept in Problem Based Learning - Kadir, Abdul; Rochmad, Rochmad; Junaedi, Iwan (Journal of Primary Education, 2020)
MMathematical connections ability is a demand in mathematics education to develop mathematical ideas and problem-solving in one another. This study aims to find mathematical connection ability patterns in terms of self-concept. The research method used is mixed methods with concurrent embedded design, quantitative research analysis using true experimental design, while qualitative research analysis uses the Miles and Huberman model. The population in this study was eighth-grade students of SMP Negeri 13 Semarang, Indonesia, and sampling was done by random sampling technique. The results showed that the mathematical connection ability pattern in terms of mathematical self-concepts is diverse. It is found that there were two patterns of mathematical connection ability in subjects with high self-concept. In subjects with moderate self-concept, three patterns of mathematical connection ability subjects with low self-concept, three patterns of mathematical connection ability are found